Identification and characterization of a novel peptide from rainbow trout (Oncorhynchus mykiss) with antimicrobial activity against Streptococcus iniae. (December 2022) - Varga, Joseph F.A.; Brunner, Sascha R.; Cheng, Grant; Min, Daniel; Aucoin, Marc G.; Doxey, Andrew C.; Dixon, Brian
Abstract: The overuse and misuse of antibiotics has led to the emergence of antibiotic-resistant bacterial species which remain a challenge to treat therapeutically. Novel and efficacious drugs are desperately needed to combat pathogens. One method to facilitate these discoveries is the use of in silico methods. Computational biology has the power to scan large data sets and screen for potential molecules with antibacterial function. In the current study, an in silico approach was used to identify an antimicrobial peptide (AMP) derived from rainbow trout von Willebrand Factor. The AMP was tested against a panel of aquatic bacterial pathogens and was found to possess antibacterial activity against Streptococcus iniae ( S. iniae ). Since S. iniae is a zoonotic pathogen, this may be useful in other species as well. The peptide was non-hemolytic and non-cytotoxic at the concentrations tested in rainbow trout cells. Pre-treatment of rainbow trout cells with the peptide did not result in an upregulation of immune genes but stimulating the rainbow trout macrophage/monocyte-like cell line, RTS11, with heat-killed S. iniae, did result in a significant upregulation of the tumor necrosis factor alpha ( tnfa ) gene. In this study, a new AMP has been identified but its expression, synthesis and role in vivo remains unknown. Nevertheless, the findings presented improve our understanding of fish gill and macrophage responses towards this important zoonotic pathogen. Highlights: rtVWF is non-hemolytic to RBCs from rainbow trout. rtVWF does not influence immune gene expression in rainbow trout cell lines. rtVWF is antibacterial towards S. iniae but not F. psychrophilum or Y. ruckeri. rtVWF does not impact the cell viability of rainbow trout cell lines. RTS-11 cells upregulate TNF alpha gene expression, when exposed to heat-killed S. iniae.